Critical Philosophy of Education: An Analysis of Paulo Freire's Thoughts on Modern Educational Practices - Saifullah, Muhammad Irsyad; Mahadi, Rahmad; Sirozi, Muhammad (Journal of Educational Sciences, 2025)
This study analyzes Paulo Freire’s philosophy of critical education and its relevance to modern educational practices, especially within the Indonesian context, by integrating it with Syed Muhammad Naquib al-Attas’s concept of ta’dīb. The background of this research is the dominance of traditional and neoliberal educational systems that often marginalize critical awareness, ethics, and spirituality in learning. The purpose of this research is to reinterpret Freire’s pedagogical framework to construct a more humanistic, dialogical, and spiritually grounded educational paradigm. Using a qualitative library research method, this study collects and analyzes primary sources from Freire’s works (Pedagogy of the Oppressed, Education for Critical Consciousness) and secondary literature from 2019–2025. The findings reveal that Freire’s key ideas, conscientização (critical consciousness), dialogue, and praxis, remain highly relevant in transforming education into a process of humanization and liberation. However, structural rigidity, exam-oriented curricula, and digital inequality still hinder its practical implementation. The synthesis of Freire’s praxis and al-Attas’s ta’dīb concept offers a holistic vision: education as both liberation from social oppression and purification of the self. The study concludes that integrating ethical and spiritual dimensions into critical pedagogy can reorient education toward forming reflective, responsible, and spiritually aware individuals, making it a transformative force for both personal and societal change.